HUBUNGAN BODY IMAGE DAN PERILAKU MAKAN MENYIMPANG DENGAN KEJADIAN OBESITAS PADA REMAJA MENENGAH DI SMA NEGERI 5 KOTA DEPOK - Siti Maulidina Tasya (2022)
Adolescents are one of the groups at risk for obesity due to changes in biological, cognitive and social forms during adolescence. These changes make teenagers begin to have an idea of how their body shape is, which is related to body image. Dissatisfaction with body shape can lead a person to behave deviantly. This study aims to determine the relationship between body image and eating disorder with the incidence of obesity in adolescents in Depok City. The study used a cross sectional design with the chi-square test method. Body image assessment was carried out using the Body Shape Questionnaire (BSQ-34) and eating disorder was carried out using the Eating Attitudes Test (EAT-26) and anthropometric measurements including weight and height of 95 students in grades X and XI of SMA Negeri 5 Depok City. The results of the analysis showed that there was a relationship between eating disorder (p = 0.000) with the incidence of obesity in students (p <0.05) and there was no relationship between body image (p = 0.276) and the incidence of obesity in students. This shows that there is a relationship between eating disorder and the incidence of obesity in students at SMA Negeri 5 Depok City.